Metrics for maternity unit staffing in low resource settings: Scoping review and proposed core indicator - Stones, William; Nair, Anjali (Frontiers in Global Women's Health, 2023)
Background The lack of usable indicators and benchmarks for staffing of maternity units in health facilities has constrained planning and effective program implementation for emergency obstetric and newborn care (EmONC) globally. Objectives To identify potential indicator(s) and benchmarks for EmONC facility staffing that might be applicable in low resource settings, we undertook a scoping review before proceeding to develop a proposed set of indicators. Eligibility criteria Population: women attending health facilities for care around the time of delivery and their newborns. Concept: reports of mandated norms or actual staffing levels in health facilities. Context studies conducted in healthcare facilities of any type that undertake delivery and newborn care and those from any geographic setting in both public and private sector facilities. Sources of evidence and charting Searches were limited to material published since 2000 in English or French, using Pubmed and a purposive search of national Ministry of Health, non-governmental organization and UN agency websites for relevant documents. A template for data extraction was designed. Results Data extraction was undertaken from 59 papers and reports including 29 descriptive journal articles, 17 national Ministry of Health documents, 5 Health Care Professional Association (HCPA) documents, two each of journal policy recommendation and comparative studies, one UN Agency document and 3 systematic reviews. Calculation or modelling of staffing ratios was based on delivery, admission or inpatient numbers in 34 reports, with 15 using facility designation as the basis for staffing norms. Other ratios were based on bed numbers or population metrics. Conclusions Taken together, the findings point to a need for staffing norms for delivery and newborn care that reflect numbers and competencies of staff physically present on each shift. A Core indicator is proposed, “Monthly mean delivery unit staffing ratio” calculated as number of annual births/365/monthly average shift staff census.